#### Answer

x = -3
y = 5

#### Work Step by Step

-x + 3y = 18
- 3x + 2y = 19
to the first equation minus 3y to both sides
-x + 3y - 3y = 18 - 3y
-x = 18 - 3y multiply by -1 both sides
-1 ( -x ) = -1 ( 18 - 3y ) use the distributive property
x = -18 + 3y substitude x to the second equation
-3 ( -18 + 3y ) + 2y = 19 use the distributive property
54 - 9y + 2y = 19
54 - 7y = 19 minus 54 to both sides
54 -7y - 54 = 19 - 54
-7y = - 35 divide by -7
$\frac{-7y}{-7}$ = $\frac{ -35}{-7}$
y = 5 substitude y = 5 to x = -18 + 3y
x = -18 + $3\times5$
x = -18 + 15
x = -3